Peranan Kepemimpinan Kepala Desa untuk Meningkatkan Partisipasi Masyarakat dalam Pembangunan Fisik Desa: Studi Kasus Pada Pemerintah Desa Bajur, Kecamatan Labuapi - Mila Pilaili; Herlina Pusparini; Nurabiah Nurabiah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2022)
This Study aims to determine the leadership role of the village head and to determine community participation in village physical development. This research is located in Bajur Village Government, Labuapi District. The research method used is a descriptive research method with a qualitative approach. The informants in this study were the village head, the village secretary, BPD, and the community as many as 14 people. This research data is primary data obtained through direct interviews with informants and strengthened by documentation. After being tested for validity, the data obtained were analyzed using data reduction, re-displaying the data, and concluding and verifying.This study uses the theory of stewardship where the results of this study indicate that there is a good relationship between the village head and the community. This can be seen from the success of a village head in carrying out his role as a motivator, facilitator, and mobilizer. Of these three indicators, the village head has carried out his duties and responsibilities as well as his role as the village head to motivate the community to jointly build the village, provide the facilities needed by the community, and provide encouragement to the community. Likewise from the community, the community is very enthusiastic about helping the village head in every village activity such as village development by participating in the planning, implementation, evaluation, and utilization stages of the results.